The Change in the Economic Status of the Low-Income Elderly in Three Industrial Countries: Circa 1979-1986 - Timothy Smeeding; Barbara Torrey; John Coder (Luxembourg Income Study (LIS), 1990)
This paper focuses on comparisons of the economic status of the elderly in Australia, Canada, and the U.S., and how it has changed in the 1980's within and between these countries.
Keywords: 330